Identifying and Addressing Childhood Food Insecurity in Healthcare and Community Settings (SpringerBriefs in Child Health,, 2018)
This salient resource offers clinicians a comprehensive multi-tiered framework for identifying, addressing, and reducing food insecurity among children and their families. Reinforcing the importance of food insecurity as a key social determinant of health, this monograph reviews the epidemiology and presents in-depth guidelines for screening for food insecurity and hunger. Recommendations for screening in a busy clinical setting as well as the strengths and limitations of widely-used instruments are discussed. The monograph also outlines a variety of clinic-level interventions, potential community-based resources, and opportunities for clinical-community partnerships to improve families' food access and security. Further, contributors provide workable plans for large-scale advocacy through greater engagement with professional and community resources as well as policymakers. The monograph concludes with an outline of the critical steps to implement a food insecurity screening process and the key components to train the next generation of provider-advocates. Included in the coverage: Epidemiology and pathophysiology of food insecurity Screening tools and training Scope of interventions to address food insecurity Creation and evaluation of the impact of food insecurity-focused clinical-community partnerships on patients and populations Development of an action plan to fight food insecurity Identifying and Addressing Childhood Food Insecurity in Healthcare and Community Settings will find an engaged audience among physicians and other clinicians who want to address food insecurity in their healthcare and/or community setting. Institutions that are starting to address social determinants of health, including food insecurity, will find guidance on screening tools, processes and evaluation of impact. .